Technology, innovation and economic policy - Hall, Peter (ed.) (New Delhi, 1986)
The processes and effects of technological change command growing attention because of their implications for employment and the future shape of society. This collection of essays reveals the diversity of current research into the process of technological innovation and the policies appropriate for its stimulation and direction. The reader is brought up to date with recent developments, with each chapter being contributed by a specialist.
Keywords: Technology and state